Inheritances in Europe: High earners reap the most benefits - Christian Westermeier; Anita Tiefensee; Markus M. Grabka (DIW Economic Bulletin, 2016)
By 2010, 27 to 40 percent of all households in euro countries had inherited or received gifts. This only includes transfers from outside their own household. The present value of these transfers averaged between 85,000 and 274,000 euros, depending on the relevant country. The sum of all inheritances and gifts in western Germany corresponds to one-third of the current net worth of households- and is the highest of all euro countries included in this study. Based on recipient households only, the share in western Germany is 52 percent. In Austria, Belgium, France, and western Germany, individuals from high-income households inherit more frequently and receive much higher amounts than those from low-income households. Since intergenerational income mobility is low, highincome households can build wealth, both from regular income and from substantial capital transfers.
Keywords: D64; D31; D14; 330; inheritances; gifts; wealth; income; HFCS; Europe